The chemokine CX3CL1 promotes intraperitoneal tumour growth despite enhanced T-cell recruitment in ovarian cancer - Seitz, Stefanie; Dreyer, Tobias F.; Stange, Christoph; Steiger, Katja; Wohlleber, Dirk; Anton, Martina; Pham, Thuý An; Sauter-Peschke, Dominique; Reuning, Ute; Multhoff, Gabriele; Weichert, Wilko; Kiechle, Marion; et al. (Neoplasia (New York, N.Y.), 2025)
T-cell recruiting chemokines are required for a successful immune intervention in ovarian cancer, and also for the efficacy of modern anticancer agents such as PARP inhibitors. The chemokine CX3CL1 recruits tumour-suppressive T-cells into solid tumours, but also mediates cell–cell adhesions, e.g. of tumour cells, through its membrane-bound form. So far, its role in ovarian cancer has only been rudimentarily addressed. We show that high CX3CL1 expression significantly correlates with worsened survival in human high-grade serous ovarian cancer (n=219). In preclinical ovarian cancer, CX3CL1 plays a dual role, as it enhances the adaptive anti-tumour response, but overall still promotes tumour growth, the latter as a feature of the intraperitoneal environment. Moreover, PARP inhibitors are able to increase CX3CL1 release from human ovarian cancer cells. Collectively, our study shows that CX3CL1 is a driver of intraperitoneal tumour growth in ovarian cancer, a feature that may compromise the anticancer effect of CX3CL1-inducing PARP inhibitors.